Trema orientalis L. and Dialium guineense Wild. used to manage hypertension in Bénin: phytochemical study and antioxidant activity - LAGNIKA, LATIFOU (My University, 2019)
Trema orientalis L. (Celtidaceae) and Dialium guineense Wild. (Caesalpiniaceae) are used traditionally as remedy against headache, pains, diarrhoea, fever and hypertension. Despite their approved efficacy there are little scientific data available on their biological potential. The present study investigated the phytochemical study and antioxidant activity of Trema orientalis and Dialium guineense. The phytochemical screening was carried out using standard procedures. The phenolic and flavonoids contents were determined using Folin-Ciocalteu and aluminium chloride reagent. The antioxidant activity was evaluated using 2, 2-diphenyl-1-picryl-hydrazyl, Ferric reducing capacity, superoxide anion and hydrogen peroxide methods. Tremas orientalis was the most active in the ferric reducing capacity with 6007.8 ± 175.57μmol AAE g-1. The superoxide anion and hydrogen peroxide scavenging activities ranged from 88.52±0.68 % to 91.33±4.01%. The DPPH scavenging activity was dose dependent. Dialium guineense was the most active with an inhibitory percentage of 96.06 ± 0.34 % comparable to ascorbic acid (99.46 ± 0.37 %).
Keywords: Dialium guineense; Trema orientalis; antioxidant